The The Effect of Tramadol Addiction on Convulsion and Related Factors - Najafi 1, Ali; Ghodrati 2, Nasrin; Zolfaghari 3, Pouneh; Salari Zare 4, Mohammad; Pourmand 5, Kamran; Sohrabi 6*, Mohammad Bagher (Shahroud Journal of Medical Sciences, 2020)
Background: Tramadol is a drug used to control severe pain. Various side effects of this drug have been reported, one of the most important is seizures. The exact cause of tramadol-induced seizures is not known. The aim of this study was to investigate the effect of tramadol addiction on convulsion and related factors in 2018.Methods: This cross-sectional study was performed on 216 patients with convulsion referred to Imam Hossain Hospital of Shahroud in 2018. After reviewing and stabilizing vital signs, a questionnaire containing demographic information, medical history, medication use (especially tramadol), and drugs was completed by patients. The association between recurrent convulsion and predictors were assessed using multivariable logistic regression. Data were analyzed and compared using SPSS statistical software, version 16 and related statistical tests. The significant level was set at 0.05.Results: In this study from 216 participants, 154 (71.3%) of them were male and the rest were female. The mean age of the all patients was 44.8±18.2 years (17-72 years) that was no significant difference between the two groups. Recurrent convulsion was significantly associated with history of opium use (Pvalue<0.032) and tramadol using (Pvalue<0.001) and there was no significant relationship with other variables. Tramadol using cans double your chances of having a recurrent convulsion [OR=2 (95% CI: 1.752 – 2.689)].Conclusions: The results of this study showed that taking tramadol in opium users can increase the incidence of recurrent convulsion, but more research is needed to fully confirm this.Key words: Tramadol, Convulsion, Side effects